MODELING THE SYSTEM OF FACTORS INFLUENCING THE INTERNATIONAL COMPETITIVENESS OF UKRAINE’S ICT SECTOR - Єлизавета Завгородня; Ярослав Шестак (Економіка та суспільство)
The article examines the structural and functional relationships among key determinants that shape the international competitiveness of Ukraine’s ICT sector. The research methodology combines graph theory and the Laurent power series. The research offers a detailed framework for understanding competitiveness in the ICT sector, highlighting the systemic interdependence among infrastructure, human capital, regulatory and business conditions, innovation potential, and international integration. It is found that the factors of the business and regulatory environment, integration of Ukraine’s ICT sector into international economic relations, and human capital have the greatest impact on the international competitiveness of the Ukrainian ICT sector. The practical value of the article lies in its applicability for strategic decision-making and policy formulation for strengthening Ukraine’s ICT sector international competitiveness, as well as further academic research and practical evaluations in similar national or regional contexts.